A utilização da variabilidade da frequência cardíaca para a prescrição individualizada do intervalo de recuperação entre as sessões de treinamento de força - Oliveira, Ramon Martins de (Universidade Federal de São Carlos, 2019)
The aim of the present study was to investigate if resistance training (RT), performed with individualized recovery between sessions (RT-IND), promotes greater gains in strength and muscle mass and reduces the variability on adaptations compared to RT with fixed recovery intervals (RT-FIX). Twenty young men (age 21.9 ± 3.3 years) were randomized in the RT-IND and RT-FIX groups. Five days before the beginning of the training, measurements of the root mean square of successive R-R intervals differences (RMSSD) values of each individual were performed to establish the baseline values. Before each RT session, the RMSSD values determined whether the participants from RT-IND protocol were recovered from the previous session. Participants performed the RT session only if RMSSD values had returned to the baseline, otherwise they had to wait for an additional 24 h. RT-FIX performed an RT session every 48 h. Muscle strength was measured by one-maximal repetition (1-RM) test and muscle cross-section area (CSA) of the vastus laterals by ultrasonography were assessed pre- and post-training. 1-RM values increased significantly from pre to post-training for both groups (RT-IND: 30% and RT-FIX: 42%, main time effect, P < 0001), with no significant difference between groups. Muscle CSA increased significantly from pre to post-training (RT-IND: 15.7% and RT-FIX: 15.8%, main time effect, P < 0001), with no significant difference between groups. In conclusion, RT-IND did not increase the gains in muscle strength and mass neither reduce the variability in muscle adaptations when compared to the RT-FIX.
Keywords: Hipertrofia; Força muscular; Frequência; Sistema nervoso autônomo; Muscle mass; Muscle strength; Frequency; Autonomic nervous system; RMSSD; CIENCIAS DA SAUDE::EDUCACAO FISICA